Perfil social e agrícola do perímetro irrigado Califórnia – Sergipe - Costa, Aldjane Moura (2015)
Irrigation in the Northeast presents itself as an alternative to counter the effects of crises in the traditional activities of the agricultural sector. Based on this premise the Government of the State of Sergipe implemented in the eighties many irrigated areas, to develop the semi-arid region, in order to increase the quality of life for residents by building on agricultural potential demonstrated by the climate, soil and availability of water for irrigation. owever, these projects have failed the success planned for various reasons. Thus, this study aims to analyze the dynamics of water, agricultural production and the profile of irrigation irrigated perimeter California, located in Canindé municipalities de San Francisco and Poço Redondo, in the extreme northwest of the state, in the semi-arid northeast. For this, there were literature surveys, desk reviews, structured interviews with questionnaires to the technical audience of local administration and the irrigators, seeking information about the type of agricultural production, social, economic and environmental. Research shows that driving the water meets technical problems especially in pumping stations resulting in lack of water for irrigation of agricultural crops. Agricultural production is shown to be diverse, but with concentration in Okra culture that predominates in most lots, to have guaranteed market. Technical assistance is cause for dissatisfaction, pointing in field research. The profile of irrigation shows that most settled in the region since the 2000s, and had cultural tradition in the primary sector of the economy also points out that between the social measures adopted, the family allowance is an important public policy and local visibility. hese considerations point to the need to problematize the development policies of the semi-arid northeast, especially the actions aimed at improving irrigated areas.